Business Intelligence (BI) Task Force @EUNIS - Cardoso, E.; Alcolea, J. J.; Rieger, B.; Schulze, S.; Rivera, M.; Leone, A.; Brighi, E. (19th EUNIS Congress "ICT Role for Next Generation Universities", 2013)
This poster presentation is to introduce both the initial objectives and activities of the new EUNIS Task Force group about the application of Business Intelligence (BI) in European Higher Education Institutions (HEI), BITF@EUNIS. Founded during the 2011 EUNIS Congress in Dublin, notable activities started as a result of a “Birds of a Feather” meeting held in Vila Real (Portugal) during the 2012 EUNIS Congress, when a group of about 19 BI enthusiasts from 9 European countries gathered to identify common topics of interest for a BI Task Force. Currently, the active members of the BI Task Force (BITF) include people from the University of Osnabrueck (Germany), the University Institute of Lisbon (Portugal), the Italian consortia AlmaLaurea and CINECA, and the Spanish Office for University Cooperation (OCU). As a starting point for further services, this core team initiated the first BITF-project to survey the occurrence and maturity of BI applications across European HEIs. Details of this survey are subject to another paper submission to EUNIS-2013. To summarize, it aims for a continuously updated collection of maturity information, enabling participants to perform a self-assessment and benchmark of its BI maturity level against other HEI, both actually and over time. Thus, it is to deliver the first cornerstone for the overall goals of the BI Task Force @EUNIS, namely, to promote the creation of a European platform to exchange and share knowledge and experiences on BI in HE institutions. Aside the maturity survey data, which of course are to be organized, processed and presented by typical BI technologies, the "BITF knowledge base" might collect and disseminate examples of BI application components or case studies as reference, e.g. data models, definitions of key measures or dimension hierarchies for analyses, or dashboard designs. Furthermore, guidelines for BI project and runtime organization are conceivable. These are just proposals for contents, which are to be defined and committed by BITF participants, next to be continued during the EUNIS 2013 conference. However, the BITF will not itself fill in the contents, in fact, it defines its responsibility only in developing and facilitating an online platform for the exchange of experiences in the sense of traditional knowledge management systems. Therefore, the directions and success are determined by its intended users, i.e. European HE institutions. With this poster, the authors want to inform about this project and invite EUNIS members for active participation in the BITF initiative.